2022
DOI: 10.3390/toxins15010007
|View full text |Cite
|
Sign up to set email alerts
|

Histone 2-Hydroxyisobutyryltransferase Encoded by Afngg1 Is Involved in Pathogenicity and Aflatoxin Biosynthesis in Aspergillus flavus

Abstract: Aflatoxin, a carcinogenic secondary metabolite produced by Aspergillus flavus, is a significant threat to human health and agricultural production. Histone 2-hydroxyisobutyrylation is a novel post-translational modification that regulates various biological processes, including secondary metabolism. In this study, we identified the novel histone 2-hydroxyisobutyryltransferase Afngg1 in A. flavus, and explored its role in cell growth, development and aflatoxin biosynthesis. Afngg1 gene deletion markedly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Here, we found that K hib ‐modified proteins were enriched in energy metabolism pathways, especially carbon fixation and glycolysis/gluconeogenesis. Microorganisms, such as Ustilaginoidea virens and Aspergillus flavus , are pathogenic to plants, and during the pathogenesis process, K hib modifications have been observed in their proteins (Chen, Li, et al., 2021; Wang, Liang, et al., 2023). Notably, the K hib ‐modified sites (such as H3K23/K36/K56/K79/K122 and H4K31/K79/K91) identified in Ustilaginoidea virens were also detected in our study, illustrating that these sites play an essential role in life activities across diverse organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that K hib ‐modified proteins were enriched in energy metabolism pathways, especially carbon fixation and glycolysis/gluconeogenesis. Microorganisms, such as Ustilaginoidea virens and Aspergillus flavus , are pathogenic to plants, and during the pathogenesis process, K hib modifications have been observed in their proteins (Chen, Li, et al., 2021; Wang, Liang, et al., 2023). Notably, the K hib ‐modified sites (such as H3K23/K36/K56/K79/K122 and H4K31/K79/K91) identified in Ustilaginoidea virens were also detected in our study, illustrating that these sites play an essential role in life activities across diverse organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , Khib modification levels were found to decrease in the absence of light [ 25 ]. Furthermore, the deletion of hydroxyisobutyryltransferase Ngg1 in Aspergillus flavus significantly reduced the aflatoxin biosynthesis when compared to WT and Afngg1 complementation strains [ 26 ]. In Ustilaginoidea virens , mutations in Khib sites in the mitogen activated protein kinase (MAPK) UvSlt2 significantly diminished fungal virulence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peanuts, with rich nutrients and health value, are a type of important oil crop [ 5 ], but they are susceptible to aflatoxin contamination. Aflatoxins, with high toxicity, teratogenicity, and carcinogenicity, have been regarded as the most toxic mycotoxins found in food and agri-food [ 6 , 7 , 8 ], which not only threaten human health, but also can lead to huge economic losses [ 9 , 10 , 11 , 12 , 13 ]. Aflatoxins are secondary metabolites, mainly produced by Aspergillus flavus (A. flavus) in food and agri-food, especially peanuts and corn [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%